Semiotics Analysis on Students’ English Textbook in Elementary School - Tri Indah Rezeki; Rakhmat Wahyudin Sagala (VELES Voices of English Language Education Society, 2021)
Textbooks are one of the main components in teaching learning activities.  It is very important that textbooks should be adjusted to the childrenâ€™s cognitive development at specific age. Semiotics is one of the aspects that can be evaluated in a textbook because the illustration of semiotics is very specific element that has great influence on childrenâ€™s visual perception. Specifically, the aim of this study is to analyze Semiotics on the studentsâ€™ English textbook in Elementary school. This study investigated the meaning of semiotics on studentsâ€™ English textbook in the second grade Elementary school and how semiotics realized on studentsâ€™ English textbook in the second grade Elementary School.  This study applied qualitative research in terms of library research to collect the data from the studentsâ€™ English textbook in the second grade Elementary school. Meanwhile, the data were analyzed by applying semiotic analysis based on the Pierceâ€™s semiotic theory namely representaman (signifier), object (referent) and interpretan (signified). The results of this study indicated that this book is very suitable for learning for the second grade students of Elementary school at SDIT Al-Hijrah 2 because the exercises contain symbols, pictures and signs that are very interesting for the second grade students of Elementary school who have high imagination. The researchers had analyzed the main pictures related to the theme of the material in the exercises. In addition, the relationship between the pictures of the exercises and the meaning is interconnected each other.